Wogonin inhibits in vitro herpes simplex virus type 1 and 2 infection by modulating cellular NF-κB and MAPK pathways - Ying Chu (BMC Microbiology, 2020)
Abstract Background Wogonin, a natural flavonoid-like chemical compound, exhibits anti-inflammatory, antitumor, antiviral, neuroprotective, and anxiolytic effects by modulating a variety of cellular signaling pathways including PI3K-Akt, p53, nuclear factor κB (NF-κB), mitogen-activated protein kinase (MAPK) pathways. In this study, its antiviral effect against herpes simplex virus (HSV) type 1 and 2 (HSV-1 and HSV-2) replication was investigated. Results Wogonin suppressed HSV-2-induced cytopathic effect (CPE) and reduced viral mRNA transcription, viral protein synthesis, and infectious virion particle titers in a dose-dependent manner. A time-of-drug-addition assay demonstrated that wogonin acted as a postentry viral inhibitor. Wogonin also significantly reduced HSV-induced NF-κB and MAPK pathway activation, which has previously been demonstrated to be important for viral replication. Conclusions Our results suggest that the anti-herpes effect of wogonin may be mediated by modulation of cellular NF-κB and JNK/p38 MAPK pathways and imply that wogonin may be useful as an anti-HSV agent.